Randomized double-blind safety comparison of intravenous iron dextran versus iron sucrose in an adult non-hemodialysis outpatient population: A feasibility study. Issue 1 (December 2016) - Louzada, Martha; Hsia, Cyrus; Al-Ani, Fatimah; Ralley, Fiona; Xenocostas, Anargyros; Martin, Janet; Connelly, Sarah; Chin-Yee, Ian; Minuk, Leonard; Lazo-Langner, Alejandro
Abstract Background Intravenous iron therapy is a treatment option for iron deficient patients who are intolerant to oral iron or where oral iron is ineffective, but with possible adverse effects. Currently, prospective studies comparing different intravenous iron formulations are needed to determine safety and efficacy of these agents. Methods We conducted a prospective, double-blind, randomized controlled trial (RCT) to assess the feasibility of a trial comparing the safety of high molecular weight intravenous iron dextran, Infufer®, with intravenous iron sucrose, Venofer®, in non-hemodialysis adult outpatients. Primary outcome was the occurrence of immediate severe drug reactions. Results We enrolled 143 patients in a one-year period. Overall, 45/143 (31.5 %) patients (20 iron dextran, 25 iron sucrose) developed 48 infusion reactions (14 immediate, 28 delayed, and 3 both). The risk of an immediate reaction was similar in both groups, 9/73 (12.3 %) iron dextran versus 8/70 (11.4 %) iron sucrose, RR = 0.93 (95 % CI; 0.38 to 2.27). The risk of a delayed reaction was significantly higher in the iron sucrose group 22/70 (31.4 %) versus the iron dextran group 9/73 (12.3 %), RR = 2.55 (95 % CI; 1.26 to 5.15;p  = 0.0078). Conclusion In this limited feasibility study, no major differences in immediate reactions were seen, but a significantly higher number of delayed reactions were seen in the iron sucrose group. Further, under our assumptions and design a full RCT to evaluate the safety of different intravenous iron preparations is not feasible. Future studies should consider modifying the clinical outcomes, utilize multiple centers, and consider other emerging parenteral iron formulations. (ClinicalTrials.gov NCT005936197 January 3, 2008).